Characteristics of effective helium source rocks and releasing mechanism of helium - Xiaofeng Wang; Dong Zhao; Dongdong Zhang; Xiaofu Li; Keyu Chen; Wenhui Liu (Journal of Natural Gas Geoscience)
Different helium source rocks exhibit varying characteristics, including differences in the content and occurrence states of precursor elements such as uranium (U) and thorium (Th). In sedimentary rocks, U and Th mainly exist in adsorbed and (or) complexed states of organic matter and clay minerals. The primary migration of helium generated in sediments is liable to occur due to the lack of mineral crystal restraint. Hence, source rocks and reservoir rocks in gas pools act as the primary effective helium source rocks in sediments. In contrast, other sedimentary rocks are less effective as helium sources due to the fact that high porosity results in prolonged helium saturation, thereby restraining the desolubilization and secondary migration of helium. In igneous rocks, isomorphous U and Th are mainly enriched in silicate and phosphate minerals. Temperature is the main controlling factor affecting their primary migration. Granite, characterized by low porosity and limited helium solubility, can experience large-scale release helium under conditions of tectonic uplift and abnormally high temperatures, acting as an effective helium source rock for helium-rich natural gases. Various forms of U and Th can exist in metamorphic rocks, which have higher porosity and higher soluble helium contents than granite, but this result in greater difficulty in helium release. Although the direct source rocks and reservoirs of natural gas reservoirs are effective helium source rocks, it is difficult to form He-rich natural gas due to the influence of hydrocarbon dilution. Sufficient He supply from basin basement or mantle-derived sources is a key condition for natural gas reservoirs to be rich in He.